Media matters race and gender in U.S. politics - Fiske, John (Routledge Taylor & Francis Group, 2016)
"Media Matters takes us to the heart of social inequality and the call for social justice by interrogating some of the most important issues of its time. Fiske offers a practical guide to learning how to interpret the ways that media events shape the social landscape, to contest official and taken-for-granted accounts of how events are presented/conveyed through media, and to affect social change by putting intellectual labor to public use. A new introductory essay by former Fiske student Black Hawk Hancock explains the theoretical and methodological tools with which Fiske approaches cultural analysis, highlighting the lessons today's students can continue to draw upon in order to understand society today."--Provided by publisher.